2020
DOI: 10.1007/s40520-020-01519-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of 6-month supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink in sarcopenic older adults

Abstract: Aims Safety and tolerability of prolonged supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink (WP-MND) was evaluated in sarcopenic older adults. Methods A 13-week double-blinded, randomized, isocaloric placebo-controlled trial (PROVIDE study; n = 380) was extended with a voluntary 13-week open-label extension (OLE). OLE participants were randomized to receive daily 1 or 2 servings of WP-MND (21 g protein, 3 g leucine, 10 µg vitD and 500 mg calcium per serving). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…In line with experimental studies and meta‐analyses of older adults who are free of renal impairment, 31 , 32 , 33 , 34 increasing protein intake well‐beyond the RDA for 16 weeks did not exert beneficial nor harmful effects on kidney function (eGFR) or whole‐body bone mass (data not shown here). The inclusion of a marker of renal function is a novelty of our study given that only 4/13 of RCTs reported on this outcome at follow‐up as highlighted in a recent meta‐analysis 11 comparing the effects of high vs. low protein diets on cardiometabolic health.…”
Section: Discussionsupporting
confidence: 83%
“…In line with experimental studies and meta‐analyses of older adults who are free of renal impairment, 31 , 32 , 33 , 34 increasing protein intake well‐beyond the RDA for 16 weeks did not exert beneficial nor harmful effects on kidney function (eGFR) or whole‐body bone mass (data not shown here). The inclusion of a marker of renal function is a novelty of our study given that only 4/13 of RCTs reported on this outcome at follow‐up as highlighted in a recent meta‐analysis 11 comparing the effects of high vs. low protein diets on cardiometabolic health.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, 16 references published for 9 RCTs met our eligibility criteria, after 40 references were excluded due to their protocols (k = 4), not RCT (k = 2), combination of medication (k = 1), and pre-sarcopenia (k = 33). All references of the nine RCTs were included ( Figure 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ageing is associated with anabolic resistance [69]. Factors such as protein intake, vitamin D/calcium, and the acid-base balance of the diet, play an important role in maintaining muscle mass and, muscle strength and physical performance [61,[70][71][72][73][74][75]. Poor nutritional status has therefore been recognised as one of the etiologic mechanisms contributing to sarcopenia [30].…”
Section: Nutrition/exercise/polypharmacy Recordmentioning
confidence: 99%